A Case-Control Study on Risk Factors of Pulmonary Infection in Patients with Type 2 Diabetes Mellitus and Its Implications for Clinical Intervention. (12th April 2022) - Li, Xue; Ren, Yanzi; Yan, Ting
Abstract : Objective. To analyze the risk factors of pulmonary infection in patients with type 2 diabetes mellitus (T2DM) and its implications for clinical intervention. Methods. One hundred and twenty-five patients with type 2 diabetes treated in our hospital from January 2019 to November 2021 were divided into simple T2DM group (n = 80 ) and infection group (n = 45 ) according to whether they were complicated with pulmonary infection or not. Sputum samples of patients with infection were collected and identified by bacterial culture. The general conditions (age, sex, body mass index, course of disease, and length of stay), pulmonary complications (chronic bronchitis, emphysema, and obstructive pulmonary disease, ), blood glucose control (fasting blood glucose and glycosylated hemoglobin), and treatment (use of hormones and antibiotics and invasive operation) were compared between the two groups. Univariate and multivariate analyses were used to screen the risk factors of pulmonary infection in patients with T2DM. Results. A total of 45 patients were found to be infected in this study. 68 pathogenic bacteria were detected in the sputum samples, of which 42 were Gram-negative (61.76%), 22 were Gram-positive (35.35%), and 4 were fungi (5.88%). Gram-negative bacteria were mainly Klebsiella pneumoniae, accounting for 25.00%, followed by Pseudomonas aeruginosa, Acinetobacter baumannii, and Escherichia coli. Gram-positive bacteria were mainly Staphylococcus aureus, accounting for 17.65%, followed by Streptococcus pneumoniae and Staphylococcus haemolyticus. The main fungi were Candida albicans (4.41%). The age, the course of T2DM, and the duration of hospitalization in the coinfection group were significantly higher than those in the T2DM group (P < 0.05 ). There was no significant difference in other indexes (P > 0.05 ). The number of patients with chronic bronchitis, emphysema, and obstructive pulmonary disease in the coinfection group was significantly higher than that in the T2DM group. The fasting blood glucose and glycosylated hemoglobin in the coinfection group were significantly higher than those in the T2DM group. The number of patients using hormone and antimicrobial agents and invasive operation in the coinfection group was higher than that in the simple T2DM group, and the difference was statistically significant (P < 0.05 ). Multivariate analysis showed that age, course of T2DM, length of hospital stay, complicated pulmonary disease, glycosylated hemoglobin, use of hormones and antibiotics, and invasive operation were all risk factors of pulmonary infection in patients with T2DM (P < 0.05 ). Conclusion. Gram-negative bacteria are the main pathogens of T2DM complicated with pulmonary infection. Drug sensitivity test should be combined to understand the drug resistance of pathogenic bacteria and use drugs reasonably to patients. Among them, advanced age, long course of T2DM, long hospital stay, complicated pulmonary disease, high level of glycosylated hemoglobin, use of hormones and antibiotics, and invasive operation were all risk factors of pulmonary infection in patients with T2DM. In clinical treatment, under the premise of using insulin to control blood sugar in an appropriate range, antibiotics should be used reasonably, pulmonary complications should be treated actively, pulmonary ventilation function should be improved, and invasive operation should be avoided as far as possible, which can effectively prevent the occurrence of T2DM complicated with pulmonary infection.